BRINGING THE REAL WORLD INTO MADRASAH CLASSROOM TEACHING INSTITUT AGAMA ISLAM NEGERI (IAIN) BENGKULU - Riswanto Riswanto (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
The paper  aimed at discussing the  nurturing  effects  of utilizing second hand  as authentic materials for encouraging English as a foreign language (EFL) learning atmosphere among  Madrasah learners. The paper was based on the community services  program conducted by writer several  months ago in collaboration with research and  community services  unit of IAIN Bengkulu.  The program involved head master, English school teacher and  90 learners of Madrasah Tsanawiyah (MTs) Mambaul  Ulum at central  Bengkulu  district.  Quasi experiment reserach design was applied  to testify the hypotheses. The raw data was analyzed  by SPSS software program. The  findings  showed that  authentic media impacts significantly towards students’  motivation and learning  achievement. The research result also proved  that the school  teachers were  motivated to design  their own classroom teaching media. In conclusion, the authentic materials bring the real world into the classroom teaching, promoting learners’ motivation and learning achievement. The last, encouraging teachers’ creativity in designing  their own media without expense